Standard kvality profesních kompetencí studenta učitelství - Kratochvílová, Jana (Masaryk University Press, 2020)
Title in English: A student teacher professional competence standard The purpose of the Standard is to describe the expert knowledge of primary and secondary school teachers, and the academic staff of the Faculty of Education about what is well-prepared implemented and assessed teaching. The Standard is primarily used by student teachers for orientation in the demands of of the quality of teaching at primary and secondary schools, for assessing and monitoring the progress of their professional competencies. Last but not least, the Standard helps to create a shared understanding of the teaching quality in the community of prospective and current teachers, thus bringing together actors involved in undergraduate training of pre-service teachers.